Dietary supplements to improve energy metabolism during long-track speed skating - Noordhof, D. A. (Sport & Geneeskunde, 2015)
The specific skating posture results in blood flow restriction in the legs, which diminishes the relative contribution of the aerobic energy system and increases the contribution of anaerobic energy systems. The purpose of this review was to summarize dietary supplements that might positively affect anaerobic energy metabolism and gross efficiency in speed skating, and to discuss the effects of these supplements on performance. Creatine, â-alanine, and sodium bicarbonate are supplements that might positively affect anaerobic energy metabolism, and dietary nitrate might influence efficiency. Based on the reviewed literature, it can be concluded that the acute effect of creatine seems trivial, but that chronic supplementation seems beneficial. Acute sodium bicarbonate supplementation is expected to result in moderate performance enhancements. Combining chronic â-alanine supplementation with acute sodium bicarbonate supplementation might have additive effects. The effectiveness of chronic â-alanine supplementation, chronic sodium bicarbonate, and acute or chronic dietary nitrate supplementation requires further investigation.